Bibliometric Analysis on the Dynamics of Income Inequality in the Digital Economy - Loso Judijanto; Irmayanti Irmayanti; Tera Lesmana (Westscience Press, 2024)
This study utilizes bibliometric analysis to explore the evolving discourse surrounding income inequality in the digital economy, identifying key thematic shifts and central scholarly contributions from 2000 to 2024. By employing VOSviewer to map keywords and author networks, the research reveals a significant transition in academic focus—from traditional aspects of economic disparity to more complex issues such as digital inequality and globalization. The findings underscore the increasing concern over how digital advancements intersect with and potentially exacerbate socioeconomic inequalities. A detailed examination of author collaborations suggests a robust, albeit evolving, network of scholarship that highlights the need for more interdisciplinary approaches and integration of emerging researchers into mainstream discourse. This study not only provides a comprehensive overview of the academic landscape but also offers insights into the practical implications for policy aimed at mitigating inequality in the digital age.